Hepatoprotective Effects of Glycyrrhetinic Acid on Lithocholic Acid-Induced Cholestatic Liver Injury Through Choleretic and Anti-Inflammatory Mechanisms - Wang, Qian; Song, Guo-Chao; Weng, Feng-Yi; Zou, Bin; Jin, Jing-Yi; Yan, Dong-Ming; Tan, Bo; Zhao, Jing; Li, Yue; Qiu, Fu-Rong (Frontiers in Pharmacology, 2022)
Cholestasis is a clinical syndrome triggered by bile acids accumulated and aggregated by subsequent inflammatory responses. The study aimed to investigate the protective effect of glycyrrhetinic acid (GA) on cholestatic liver injury induced by LCA from both anti-inflammatory and choleretic mechanisms. Male C57BL/6 mice were treated with LCA twice daily for 4 days to induce intrahepatic cholestasis. GA (50 mg/kg) and pregnenolone 16 α-carbonitrile (PCN, 45 mg/kg) were intraperitoneally injected 3 days before and throughout the administration of LCA, respectively. Plasma biochemical indexes were determined by assay kit and hepatic bile acids were quantified by LC-MS/MS. H&E staining of liver sections was performed for pathological examination. Protein expression of TLRs/NF-κB pathway and mRNA levels of inflammatory cytokines and chemokines were examined by Western blotting or PCR. Hepatic expression of pregnane X receptor (PXR), farnesoid X receptor (FXR) and their target genes of metabolic enzymes and transporters were evaluated. GA significantly reversed liver necrosis and decreased plasma ALT and ALP activity. Plasma total bile acids, total bilirubin, and hepatic bile acids were also remarkably reserved. More importantly, recruitment of inflammatory cells to hepatic sinusoids was alleviated. Additionally, protein expression of TLR2, TLR4 and p-NF-κBp65, and mRNA expression of CCL2, CXCL2, IL-1β, IL-6, and TNF-α were significantly decreased. Moreover, GA significantly increased the expression of hepatic FXR and its target genes including BSEP, MRP3 and MRP4. GA has a protective effect against LCA-induced cholestatic liver injury, owing to inhibition of the TLRs/NF-κB pathway and up-regulation of hepatic FXR expression.